Psychological fortitude model for digitally mindset working adults - Potgieter, Ingrid; Ferreira, Nadia (Frontiers in Psychology, 2022)
The inception of Industry 4.0 (which includes smart digital technologies and intelligence), as well as the rapidly enforced adoption of the technological revolution due to the lockdown regulations during the COVID-19 pandemic, brought new situational demands, challenges and opportunities for both employees and organisations across the globe. Individuals are required to develop personal enablers (both intrapersonal and intradigital attributes) to optimise their psychological fortitude. Research on the intrapersonal resources needed by employees to have the fortitude to adapt to remote working conditions as a result of the digital era, is currently lacking. The digital era brought about the question of how individuals’ career adaptability and career wellbeing (as a set of agile adaptable attributes) relate to their perceptions of the value-oriented psychological contract, and whether these intrapersonal resources can contribute to a psychological fortitude model for remote working employees. This study utilised a survey method to investigate the correlations between agile adaptable attributes and the value-oriented psychological contract of global digital-mindset human resource and financial service organisations. Based on further canonical correlations, structural equation modelling was conducted to develop and recommend a psychological fortitude model for remote working adults in the digital age. Close theoretical and empirical associations were found between career adaptability and career wellbeing (as agile adaptable variables) and the perceived value-orientated psychological contract. This study proposed a psychological fortitude model (consisting of intrapersonal resources) that organisations and career practitioners can use as a basis to enhance employees’ psychological fortitude in the digital age, as well as for further career research.